Apprenticeship training in Italy - a cost-effective model for firms? - Mühlemann, Samuel [Verfasser]; Wolter, Stefan C. [Verfasser]; Joho, Eva [Verfasser] (Bertelsmann Stiftung, 2018)
"Countries with a high proportion of young people choosing apprenticeship training rather than either general education or full-time schooling options have not only demonstrated low youth unemployment rates but also distinctively lower ratios of youth unemployment relative to the overall unemployment rates of the country. Therefore, many people consider apprenticeship training as a possible and potentially powerful solution to the problem of an often prolonged and difficult transition for youths from school to the labour market. In recent reports, the OECD diagnosed substantial skills mismatch and skills shortages in Italy, and also proposed to improve the quality of apprenticeship training in Italy, and to promote the dual form of apprenticeship training. However, apprenticeship systems demand the high involvement of firms, which is not common in countries that do not have a long tradition of apprenticeship training (as is the case in Switzerland or Germany, for example). As many firms fear the costs of training apprentices, and despite political support, the dissemination of apprenticeship models has not enjoyed much success in the last ten years. If one wants to increase the popularity of the apprenticeship type of training, it is important to provide reliable information to firms about circumstances in which apprenticeship models are a potential win-win-win situation, creating benefits not only for individuals and the state, but also for the training firms. One way of doing this is to measure the costs and benefits of firms that train apprentices; however, representative data are currently only available for Germany and Switzerland and, more recently, for Austria. In this study, we will - for several reasons - not measure the costs and benefits of existing training schemes in Italy, but instead simulate the costs and benefits for Italian firms that would train in one of nine occupations in very different economic sectors. This study therefore analyses the question of whether an average Italian firm could expect a net benefit when training apprentices in a similar manner to Swiss firms." (excerpt; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; I 2.2.1 Westeuropa; Berufsausbildung; Betriebliche Berufsausbildung; Ausbildungskosten; Nutzen; Kosten-Nutzen-Analyse; Szenario; Italien